Oral and systemic HPV antibody kinetics post-vaccination among HIV-positive and HIV-negative men. Issue 18 (24th April 2019) - Pinto, Ligia A.; Wilkin, Timothy J.; Kemp, Troy J.; Abrahamsen, Martha; Isaacs-Soriano, Kimberly; Pan, Yuanji; Webster-Cyriaque, Jennifer; Palefsky, Joel M.; Giuliano, Anna R.
Abstract: Duration and functional aspects of the oral and systemic antibody responses following HPV vaccination in HIV-negative (HIV − ) and HIV-positive (HIV + ) men are not well characterized. Oral and systemic HPV-16 and HPV-18-specific antibody levels were evaluated over 18-months of follow-up, in HIV + and HIV − men. Sera and oral gargles from 147 HIV − men, ages 27–45 and 75 HIV + men, ages 22–61, who received 3-doses of quadrivalent HPV vaccine were tested for HPV-16 and HPV-18 antibodies at Day 1, Month 7 (1 month post-dose 3), and Month 18 (12 months post-dose 3) and HPV avidity (Day 1, and Month 7) using L1-VLP ELISA. All individuals seroconverted, regardless of HIV-status, following 3-doses of vaccine for HPV-16 and HPV-18. Serum HPV-16 and HPV-18 antibody geometric mean levels were >2-fold lower in HIV + compared to HIV − men at Month 7 (HPV-16: 808.5 versus 2119.8 EU/mL, and HPV-18: 285.8 versus 611.6 EU/mL, p < 0.001) but not significantly different at Month 18 (HPV-16: 281.8 versus 359.7 EU/mL, p = 0.145, and HPV-18: 120.2 versus 93.4 EU/mL, p = 0.372). Post-vaccination, only oral HPV-16 antibody levels at Month 7 were significantly different between HIV + and HIV − men (127.7 versus 177.1 EU/mg of IgG, p = 0.008). Among baseline HPV-seronegative men, circulating levels of HPV-16 and HPV-18 antibodies were up to >3 fold lower in HIV + men, at Months 7 and 18. In contrast, levels of HPV-16 and HPV-18 antibodies after vaccination were not inferior in baseline HPV-seropositive, HIV + men. HPV-16 and HPV-18 avidity was lower among HIV + compared to HIV − men at Month 7 (HPV-16: 1.95 M versus 2.12 M, p = 0.027; HPV-18: 1.50 M versus 1.72 M, p < 0.001). Although differences in peak antibody levels were observed between HIV + and HIV − men following 3 doses of vaccine, plateau antibody levels were overall comparable, and avidity was relatively high for both groups. These data indicate that the vaccine induced antibody affinity maturation in both HIV + and HIV − men and will likely result in long-term protective immune responses.